Volumetric Contrast‐Enhanced Ultrasound Imaging of Renal Perfusion. (1st August 2014) - Mahoney, Marshall; Sorace, Anna; Warram, Jason; Samuel, Sharon; Hoyt, Kenneth
Abstract : Objectives: To determine whether volumetric contrast‐enhanced ultrasound (US) imaging has the potential to monitor changes in renal perfusion after vascular injury. Methods: Volumetric contrast‐enhanced US uses a series of planar image acquisitions, capturing the nonlinear second harmonic signal from microbubble contrast agents flowing in the vasculature. Tissue perfusion parameters (peak intensity [IPK ], time to peak intensity [TPK ], wash‐in rate [WIR], and area under the curve [AUC]) were derived from time‐intensity curve data collected during in vitro flow phantom studies and in vivo animal studies of healthy and injured kidneys. For the flow phantom studies, either the contrast agent concentration was held constant (10 μL/L) with varying volumetric flow rates (10, 20, and 30 mL/min), or the flow rate was held constant (30 mL/min) with varying contrast agent concentrations (5, 10, and 20 μL/L). Animal studies used healthy rats or those that underwent renal ischemia‐reperfusion injury. Renal studies were performed with healthy rats while the transducer angle was varied for each volumetric contrast‐enhanced US image acquisition (reference or 0°, 45°, and 90°) to determine whether repeated renal perfusion measures were isotropic and independent of transducer position. Blood serum biomarkers and immunohistology were used to confirm acute kidney injury. Results: Flow phantom results revealed a linear relationship between microbubble concentrations injected into the flow system and the IPK, WIR, and AUC ( R 2 > 0.56; P < .005). Furthermore, there was a linear relationship between volume flow rate changes and the TPK, WIR, and AUC ( R 2 > 0.77; P < .005). No significant difference was found between the transducer angle during data acquisition and any of the perfusion measures ( P > .60). After induction of renal ischemia‐reperfusion injury in the rat animal model (n = 4), volumetric contrast‐enhanced US imaging of the injured kidney revealed an initial reduction in renal perfusion compared to control animals, followed by progressive recovery of vascular function. Conclusions: Volumetric contrast‐enhanced US–based renal perfusion imaging may prove clinically feasible for detecting and monitoring acute kidney injury.